Relationship Between Visceral Infarction and Ischemic Stroke Subtype. Issue 3 (March 2018) - Finn, Caitlin; Hung, Peter; Patel, Praneil; Gupta, Ajay; Kamel, Hooman
Abstract : Background and Purpose—: Most cryptogenic strokes are thought to have an embolic source. We sought to determine whether cryptogenic strokes are associated with visceral infarcts, which are usually embolic. Methods—: Among patients prospectively enrolled in CAESAR (Cornell Acute Stroke Academic Registry), we selected those with a contrast-enhanced abdominal computed tomographic scan within 1 year of admission. Our exposure variable was adjudicated stroke subtype per the Trial of ORG 10172 in Acute Stroke Treatment classification. Our outcome was renal or splenic infarction as assessed by a single radiologist blinded to stroke subtype. We used Fisher exact test and multiple logistic regression to compare the prevalence of visceral infarcts among cardioembolic strokes, strokes of undetermined etiology, and noncardioembolic strokes (large- or small-vessel strokes). Results—: Among 227 patients with ischemic stroke and a contrast-enhanced abdominal computed tomographic scan, 59 had a visceral infarct (35 renal and 27 splenic). The prevalence of visceral infarction was significantly different among cardioembolic strokes (34.2%; 95% confidence interval [CI], 23.7%–44.6%), strokes of undetermined etiology (23.9%; 95% CI, 15.0%–32.8%), and strokes from large-artery atherosclerosis or small-vessel occlusion (12.5%; 95% CI, 1.8%–23.2%; P =0.03). In multiple logistic regression models adjusted for demographics and vascular comorbidities, we found significant associations with visceral infarction for both cardioembolic stroke (odds ratio, 3.5; 95% CI, 1.2–9.9) and stroke of undetermined source (odds ratio, 3.3; 95% CI, 1.1–10.5) as compared with noncardioembolic stroke. Conclusions—: The prevalence of visceral infarction differed significantly across ischemic stroke subtypes. Cardioembolic and cryptogenic strokes were associated with a higher prevalence of visceral infarcts than noncardioembolic strokes. Abstract : Supplemental Digital Content is available in the text.